Malignant Peripheral Nerve Sheath Tumor of the C2 Nerve Root: Case Report - Joshua D. Burks; Robert G. Briggs; Chad A. Glenn; John C. Greenert; Cordell M. Baker; Keren Bartal; Greg A. Krempl; Michael E. Sughrue (Journal of Neurological Surgery Reports, 2017)
Abstract Here we present the case of a 36-year-old man who was found to have a symptomatic malignant neural sheath tumor growing from the C2 nerve root following a period of progressively worsening headaches. The patient was successfully treated with surgical resection resulting in resolution of cranial nerve deficits. Though uncommon, malignant peripheral nerve sheath tumor must be considered in the differential diagnosis of tumors involving the cervical nerve roots and carotid space.